Fracture failure analysis of hard and thick key layer and its dynamic response characteristics. (April 2019) - Jiang, Lishuai; Wu, Quansen; Wu, Quanlin; Wang, Pu; Xue, Yanchao; Kong, Peng; Gong, Bin
Abstract: Igneous rock often appears in coal measure strata, and its occurrence, size, and distribution play important roles in mining safety. The failure of hard and thick igneous rocks can result in dynamic disasters such as rock burst, mine seismicity, gas outburst, and surface subsidence, all of which seriously threaten the safety of mine production. The fracture failure step distance of the hard and thick igneous rock was deduced based on the occurrence law of microseismic (MS) events, the characteristics of surface subsidence, and the change law of support resistance in the 10416 working face at Yangliu coal mine (YLCM). And this study used the theoretical analysis method to deduce the calculation method of the fracture failure of hard and thick key strata. Based on plate yield line theory and the energy method, the hard, thick critical layer collapse mechanism and the calculation expression of fracture step distance were obtained under the condition that three edges are clamped and one edge is simply supported. The fracture failure step distance of the hard and thick igneous rock that was obtained through field measurement and analysis were approximately identical with those calculated by the theoretical formula, verifying the accuracy of the theoretical calculation process and the results. Results of this study can guide the prevention and control of dynamic disasters and the roadway support design under the condition of overlaying the hard and thick key layer on the working face. Highlights: The calculation method of the fracture failure of hard and thick key strata is obtained by theoretical analysis. In situ investigations are performed into the progressive fracture failure procedure. The field observation result is similar to the theory analysis result.